2013
DOI: 10.1111/efp.12045
|View full text |Cite
|
Sign up to set email alerts
|

First report of Bursaphelenchus hellenicus Skarmoutsos, Braasch, Michalopoulou (Nematoda: Aphelenchoididae) from Turkey

Abstract: A survey was conducted in forest sites of the Mu gla Regional Forest Directorates for the presence of the pinewood nematode, Bursaphelenchus xylophilus. Wood samples were collected from declining pine and cedar trees. A total of 207 samples were taken, and nematodes were extracted, observed and identified. The pinewood nematode was not detected, but another Bursaphelenchus species was recovered from the wood of a Pinus brutia tree in Es ßen-Karadere location in Fethiye, which strongly resembled the original de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Bursaphelenchus species in coniferous forests of Turkey (Akbulut et al, 2006;Akbulut, Braasch et al, 2007;Akbulut, Elekcioglu et al, 2007;Akbulut, Vieira et al, 2008;Akbulut, Elekcioglu et al, 2008;Akbulut, et al, 2013…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bursaphelenchus species in coniferous forests of Turkey (Akbulut et al, 2006;Akbulut, Braasch et al, 2007;Akbulut, Elekcioglu et al, 2007;Akbulut, Vieira et al, 2008;Akbulut, Elekcioglu et al, 2008;Akbulut, et al, 2013…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, survey studies were carried out to investigate the presence of the pinewood nematode in the coniferous forests of Turkey. As a result of these studies, several Bursaphelenchus species were identified from conifer tree species, but not B. xylophilus (Akbulut et al, 2006; Akbulut, Braasch et al, 2007; Akbulut, Elekcioglu et al, 2007; Akbulut, Vieira et al, 2008; Akbulut, Elekcioglu et al, 2008; Akbulut, et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…anamurius, B. andrassyi, B. hellenicus, B. mucronatus, B. pinophilus, B. sexdentati andB. vallesianus, (Akbulut et al, 2006, Akbulut et al, 2007;Akbulut et al, 2008a;Akbulut et al, 2008b;Akbulut et al, 2013, Dayi et al, 2014. However, no insect species have been reported as vectors of these Bursaphelenchus species in Turkey except the report of M. galloprovincialis as the vector of B. mucronatus (Akbulut et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also observed during the survey of B. xylophilus. Since 2002, over 3000 wood samples around Turkey were taken from dead or dying conifer species, and only 5 % of the total samples was contained Bursaphelenchus species with limited number of individuals (Akbulut et al, 2006;Akbulut et al, 2007;Akbulut et al, 2008a;Akbulut et al, 2013). All reported Bursaphelenchus species are believed to be native to Turkish conifer forests, and no extensive wilting symptoms caused by these Bursaphelenchus species have been observed so far.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, several monitoring surveys are continuously performed in natural forests, yielding new observations on the distribution of Bursaphelenchus spp. all over the world and description of new species of the genus (Philis & Braasch, 1996; Braasch and Schmutzenhofer, 2000; Pedram et al., 2011, Akbulut, Braasch, & Cebeci, 2013; Inácio et al. 2015; Inácio, Nóbrega, Mota, & Vieira, 2017; Miraeiz et al., 2015; Tomalak and Pomorski, 2015; etc.).…”
Section: Introductionmentioning
confidence: 99%